Pharmaceutical study of Teucrium eriocephalum. I Study of the antiseptic power - Miranda, C.; Suñé, J. Mª (Ars Pharmaceutica (Internet), 1969)
1. The antiseptic power of the essence Teucrium eriocephalum on Escherichia coli and on Stafilococus aureus is proven, demonstrating a good antiseptic power over the former, even at concentrations of 1.75 x 10-3 and antiseptic power only regular against staphylococcus a same concentration. 2...